Consumer Attitudes Toward Green Marketing: A Study With Particular Reference To The Kozhikode District - E, Ashraf.; T, Majeesh. (International Journal of Psychosocial Rehabilitation, 2024)
According to SHIL (2012), "green marketing" is referred to as the advertising of products that are deemed to be environmentally friendly. This essay seeks to examine consumer attitudes toward environmentally friendly marketing strategies and gauge customer knowledge of such strategies. Sujith T. S.'s questionnaire approach, introduced in 2017, was used to gauge attitudes toward green practices. Based on the main information gathered from clients in the Kozhikode District, this study is analytical and descriptive. 120 consumers were chosen at random for the survey's sample size, which was handled individually. This study’s results demonstrated that consumers had a very high level of knowledge regarding green marketing. Additionally, the consumer's perspective on the significance of using green marketing techniques and attitude.